Assistive technology provision: towards an international framework for assuring availability and accessibility of affordable high-quality assistive technology - de Witte, Luc; Steel, Emily; Gupta, Shivani; Ramos, Vinicius Delgado; Roentgen, Uta (Disability and rehabilitation: Assistive technology, 2018)
Purpose: This is a position paper describing the elements of an international framework for assistive technology provision that could guide the development of policies, systems and service delivery procedures across the world. It describes general requirements, quality criteria and possible approaches that may help to enhance the accessibility of affordable and high quality assistive technology solutions. Materials and methods: The paper is based on the experience of the authors, an analysis of the existing literature and the inputs from many colleagues in the field of assistive technology provision. It includes the results of discussions of an earlier version of the paper during an international conference on the topic in August 2017. Results and conclusion: The paper ends with the recommendation to develop an international standard for assistive technology provision. Such a standard can have a major impact on the accessibility of AT for people with disabilities. The paper outlines some the key elements to be included in a standard. Implications for Rehabilitation Assistive technology is a key element in rehabilitation, but many people have no access to affordable AT solutions. The recommendations in the paper aim to inform policies, systems and service delivery procedures on how to improve access to AT across the world.